1981
DOI: 10.1021/jf00103a004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultra-high-temperature pasteurization on milk proteins

Abstract: Ultra-high-temperature (UHT) pasteurization of skim milk (148 °C for 3 s) has been found to inactivate effectively foot and mouth disease virus. For determination of the effect of UHT pasteurization on milk proteins, the composition and properties of proteins from milk after this treatment were compared with those from conventional high-temperature-short-time pasteurized (HTST = 71.7 °C for 15 s) and raw skim milks. Vacuum-dried-acid-precipitated caseins and freeze-dried-dialyzed whey proteins were prepared fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 11 publications
3
32
0
Order By: Relevance
“…A green colour or a sulphur smell are related to the characteristic appearance of rotten eggs, and indicate the end of shelflife. Changes in egg rheological behaviour are also typically associated to protein denaturation, and may occur during pasteurization (Douglas, Greenberg, Farrell, & Edmondson, 1981) and egg irradiation with ionising sources (Min et al, 2005). Consequently, in the present study, the consumer acceptance of egg fractions treated with different methods was evaluated by asking the degree of liking on 9-point hedonic scales for 5 different parameters: colour, aroma, viscosity, appearance and general acceptance.…”
Section: Consumer Acceptance Testmentioning
confidence: 99%
“…A green colour or a sulphur smell are related to the characteristic appearance of rotten eggs, and indicate the end of shelflife. Changes in egg rheological behaviour are also typically associated to protein denaturation, and may occur during pasteurization (Douglas, Greenberg, Farrell, & Edmondson, 1981) and egg irradiation with ionising sources (Min et al, 2005). Consequently, in the present study, the consumer acceptance of egg fractions treated with different methods was evaluated by asking the degree of liking on 9-point hedonic scales for 5 different parameters: colour, aroma, viscosity, appearance and general acceptance.…”
Section: Consumer Acceptance Testmentioning
confidence: 99%
“…Whey protein nitrogen analysis shows significant protein denaturation. No significant losses in nutritive values were found, and differences in viscosity and emulsification· capacity were small (Douglas et al, 1981). It has been suggested that residual plasmin activity (this enzyme is fairly heatresistant) in UHT milk may be one otthe factors of late gelation during storage.…”
Section: Determination Of Some Indigenous Milk Enzymesmentioning
confidence: 99%
“…For example, a-lactalbumin is more susceptible to denaturation in milk than in whey, but the opposite is true of ,B-Iactoglobulin (Elfagam and Wheelock 1977). Many factors influence milk stability in these complex systems (Holt et al 1978;Pyne and McHenry 1955;Rose 1961A,B, 1963Sweetsur and White 1974;Tessier and Rose 1964) during heat treatments, ranging from 72°C for 15 sec for pasteurization to 120°C for 20 min or 142°C for several seconds for sterilization (Creamer and Matheson 1980;Douglas et al 1981). Casein is most important in determining the properties of milk products because of its high concentration (Payens 1978), but ,B-Iactoglobulin has a larger effect on a molar basis (de Wit 1981;Fox and Morrissey 1977;Rose 1961A,B, 1963.…”
Section: General Commentsmentioning
confidence: 99%